Homology between SARS CoV-2 and human proteins - Vladimir Khavinson (Nature Portfolio, 2021)
Abstract An extremely high contagiousness of SARS CoV-2 indicates that the virus developed the ability to deceive the innate immune system. The virus could have included in its outer protein domains some motifs that are structurally similar to those that the potential victim's immune system has learned to ignore. The similarity of the primary structures of the viral and human proteins can provoke an autoimmune process. Using an open-access protein database Uniprot, we have compared the SARS CoV-2 proteome with those of other organisms. In the SARS CoV-2 spike (S) protein molecule, we have localized more than two dozen hepta- and octamers homologous to human proteins. They are scattered along the entire length of the S protein molecule, while some of them fuse into sequences of considerable length. Except for one, all these n-mers project from the virus particle and therefore can be involved in providing mimicry and misleading the immune system. All hepta- and octamers of the envelope (E) protein, homologous to human proteins, are located in the viral transmembrane domain and form a 28-mer protein E14-41 VNSVLLFLAFVVFLLVTLAILTALRLCA. The involvement of the protein E in provoking an autoimmune response (after the destruction of the virus particle) seems to be highly likely. Some SARS CoV-2 nonstructural proteins may also be involved in this process, namely ORF3a, ORF7a, ORF7b, ORF8, and ORF9b. It is possible that ORF7b is involved in the dysfunction of olfactory receptors, and the S protein in the dysfunction of taste perception.